LARANGAN PELAKU USAHA TERHADAP IKLAN PRODUK YANG MENYESATKAN KONSUMEN - Yuliska, Edwin (Normative Jurnal Ilmiah Hukum, 2023)
Product information to consumers must be correct, clear and honest, so that consumers do not suffer losses and product guarantees can be fulfilled according to consumer demand and legislation. However, there are still business actors advertising their products with misleading advertisements, so it is very interesting to discuss and set forth in a normative journal with the title Prohibition of business actors on misleading product advertisements. Whereas as regulated in the articles above, the responsibilities of advertising business actors are also based on the existence of a legal relationship between consumers and business actors. The legal relationship does not only cover the legal relationship that arises immediately when an agreement is made, in this case regarding all matters relating to the product, between the consumer and the business actor, but also includes the legal relationship that arises because of the law.